SPEECH ETIQUETTE AND ITS RELATION TO HISTORICAL CULTURE IN ENGLISH AND UZBEK LANGUAGE SYSTEMS - Ibrohimova, H.M. (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
This dissertation investigates the linguistic and sociocultural nature of speech etiquette in English and Uzbek, examining how communicative norms, historical traditions, and cultural values shape the structure and function of polite interaction in both languages. Speech etiquette is conceptualized as a system of conventionalized linguistic formulas and behavioral strategies that regulate interpersonal communication, ensure social harmony, and reflect collective worldviews. Although universal in its communicative purpose, speech etiquette manifests differently across languages due to variations in cultural heritage, religious beliefs, social hierarchy, and communicative expectations. The study also considers the impact of globalization, digital communication, and intercultural contact on the transformation of etiquette systems. While English elements are increasingly integrated into modern Uzbek discourse, nationally embedded forms of politeness continue to serve as essential markers of cultural identity. Overall, the dissertation argues that speech etiquette represents a dynamic intersection of language, culture, and social structure. The comparative insights obtained contribute to linguistic pragmatics, intercultural communication studies, and the broader understanding of cultural identity in a globalizing world.